Pemeliharaan dan Perawatan pada Pompa Ipam Ngagel 1 - Barokah, Ahmad Wiji; Ashari, Faisal (Universitas Bojonegoro, 2022)
The Regional Drinking Water Company (PDAM) of the City of Surabaya is a company that produces clean water in Surabaya so that there are often problems with the production system, including damage to a device such as a pump. Pump is a tool or machine used to move liquids from one place to another. If the maintenance is appropriate and planned, the obstacles and problems that arise are not getting more and the budget is getting smaller. The purpose of this study is to find out the types of water pumps in IPAM NGAGEL 1 PDAM Surya Sembada Surabaya, find out how to repair the water pump at IPAM NGAGEL 1 PDAM Surya Sembada Surabaya, and know the maintenance and maintenance of water pumps at IPAM NGAGEL 1 PDAM Surya Sembada Surabaya. The power collection method used is the direct participation of researchers on the object of research, observations and interviews with the field responsible for managing the maintenance of the pump in IPAM NGAGEL 1 PDAM Surya Sembada Surabaya. From the results of the research conducted, it was found that in IPAM Ngagel 1 PDAM Surya Sembada itself the pumps are divided into 2 types of pumps, namely raw water pumps (PS) and distribution pumps (PK). On the one hand, the recommended maintenance in order to extend the life of the pump is a scheduled monitor once a week covering electrical and mechanical, scheduled maintenance once a week includes cleanliness, bolt tightness, religment, and greasing, the last is the need for a personal complaint procedure in the form of application complaints (personal assistance) and asset management applications (Asset Management).